(untitled) (Technological Innovations Journal, 2024)
The clarity of the conceptions of reading comprehension and its levels in coherence to the measurement evaluations are essential, in the context where technology and digitized reading prevail. Objective: to identify and deepen the current conceptions of the levels of reading comprehension and the use of the Padlet in the educational field. Methodology: Qualitative approach, documentary research, a non-systematic, selective review was carried out under inclusion criteria in databases such as Scielo, Google Scholar, Dialnet, among others. Results: The use of the Padlet is presented as one of the alternatives to improve the levels of reading comprehension as benefits according to the cybernetic age. Mainly due to its great adaptability to various formats, interactivity, the wall of words, uploading and downloading of texts and links, collaborative work, metacognition, recording, construction of schemes, etc. Conclusions: The benefits of the Padlet are likely to be used as reading strategies advocating a better understanding for critical-reflexive thinking.